Closed cranial window rodent model for investigating hemodynamic response to elevated intracranial pressure. Issue 4 (19th November 2021) - Oberdier, Matt T.; Antaki, James F.; Kharlamov, Alexander; Jones, Stephen C.
Abstract: Background: Elevated intracranial pressure (ICP) occurs in several physiological and pathological conditions, yet long‐term sequellae are not common, which implies that blood flow is preserved above ischemic thresholds. Methods: This pilot study sought to confirm this hypothesis using a closed cranial window model in a rat in which ICP was elevated to 120 mmHg for 12 min, and superficial cortical perfusion was measured by laser Doppler flowmetry and laser speckle flowmetry. Results: Following a transient increase, cortical blood flow decreased to between 25% and 75% of baseline. These levels correspond to disrupted metabolism and decreased protein synthesis but did not exceed thresholds for electrical signaling or membrane integrity. This may partially explain how some episodes of elevated ICP remain benign. Conclusion: The closed cranial window model provides a platform for prospective study of physiologic responses to artificially elevated ICP during neurosurgery to promote hemostasis.